Frequent Emergency Department Use by Children. Issue 12 (15th December 2021) - Vivier, Patrick M.; Rogers, Michelle L.; Gjelsvik, Annie; Linakis, James G.; Schlichting, Lauren E.; Mello, Michael J.
Abstract : Objectives: Frequent use of the emergency department (ED) is often targeted as a quality improvement metric. The objective of this study was to assess ED visit frequency by the demographic and health characteristics of children who visit the ED to better understand risk factors for high ED utilization. Methods: The majority of pediatric ED services in Rhode Island are provided by a hospital network that includes the state's only children's hospital. Using 10 years of data (2005–2014) from this statewide hospital network, we examined ED use in this network for all children aged 0 to 17 years. Patients' home addresses were geocoded to assess their neighborhood characteristics. Results: Between 2005 and 2014, 17, 844 children visited 1 or more of the network EDs at least once. In their year of maximum use, 67.8% had only 1 ED visit, 20.1% had 2 visits, 6.9% had 3 visits, and 5.2% had 4 or more visits. In the adjusted multinomial logistic regression model, age, race/ethnicity, language, insurance coverage, medical complexity, neighborhood risk, and distance to the ED were found to be significantly associated with increased visit frequency. Conclusions: Risk factors for frequent ED use by children include age, race/ethnicity, language, insurance coverage, medical complexity, neighborhood risk, and distance to the hospital. To decrease frequent pediatric ED use, improved medical management of complex medical problems is needed, but it is also essential to address modifiable social determinants of health care utilization in this population.